Disparities in Fruits and Vegetables Consumption in Houston, Texas - Vishnu P. Nepal MSc, MPH; Osaro Mgbere PhD, MPH; Deborah Banerjee PhD, MS; Raouf R. Arafat MD, MPH (SAGE Publishing, 2011)
Background: The consumption of the recommended amount of fruits and vegetables is believed to help prevent nutrient deficiency disorders and lower the risk of several chronic diseases. Information on the disparity of fruit and vegetable consumption may be useful in designing targeted health promotion programs for increasing fruit and vegetable consumption. The objective of this pilot study was to examine disparities in fruit and vegetable consumption among Houston residents based on sociodemographic characteristics. Methods: The authors conducted bivariate and multivariate analyses to examine the associations between sociodemographic characteristics and fruit and vegetable consumption using a random digit dialing (RDD) health survey data (N = 1001) collected in Houston, Texas. Results: Bivariate analysis showed that there were significant associations between fruit and vegetable consumption and education ( P < .01); race/ethnicity ( P < .001); marital status ( P < .001); and employment status ( P < .05). Multivariate analysis indicated that fruit and vegetable consumption pattern could be significantly ( P ≤ .05) predicted by gender, race, and marital status. Respondents who were of other race category were less likely than whites to consume fruits and vegetables, while married respondents and women were more likely to consume fruits and vegetables compared to the unmarried and men, respectively. Implications: Health promotion programs aimed at increasing the consumption of fruits and vegetables should consider developing targeted intervention for men, people with less formal education, minority race/ethnicity, people who are unemployed, and those who are unmarried.